Issues Related to Text Comprehensibility: The Future of Readability - Zakaluk, Beverley; Samuels, S. (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1996)
ABSTRACTThis paper places readability in an historical context, reviews the development of present day formulas and their liabilities, explores other factors that influence meaning making, and considers comprehensibility from the point of view of the educator. The authors conclude that determining how easy or how difficult a particular book may be for a particular reader is a complex task. There may be a time when it is possible to develop a formula that includes all elements that impact upon readability, but at present, estimating text comprehensibility requires personal judment.